A multiscale modeling framework model (superparameterized CAM5) with a higher‐order turbulence closure: Model description and low‐cloud simulations. (18th April 2015) - Wang, Minghuai; Larson, Vincent E.; Ghan, Steven; Ovchinnikov, Mikhail; Schanen, David P.; Xiao, Heng; Liu, Xiaohong; Rasch, Philip; Guo, Zhun
Abstract In this study, a higher‐order turbulence closure scheme, called Cloud Layers Unified By Binormals (CLUBB), is implemented into a Multiscale Modeling Framework (MMF) model to improve low‐cloud simulations. The performance of CLUBB in MMF simulations with two different microphysics configurations (one‐moment cloud microphysics without aerosol treatment and two‐moment cloud microphysics coupled with aerosol treatment) is evaluated against observations and further compared with results from the Community Atmosphere Model, Version 5 (CAM5) with conventional cloud parameterizations. CLUBB is found to improve low‐cloud simulations in the MMF, and the improvement is particularly evident in the stratocumulus‐to‐cumulus transition regions. Compared to the single‐moment cloud microphysics, CLUBB with two‐moment microphysics produces clouds that are closer to the coast and agrees better with observations. In the stratocumulus‐to‐cumulus transition regions, CLUBB with two‐moment cloud microphysics produces short‐wave cloud forcing in better agreement with observations, while CLUBB with single‐moment cloud microphysics overestimates short‐wave cloud forcing. CLUBB is further found to produce quantitatively similar improvements in the MMF and CAM5, with slightly better performance in the MMF simulations (e.g., MMF with CLUBB generally produces low clouds that are closer to the coast than CAM5 with CLUBB). Improved low‐cloud simulations in MMF make it an even more attractive tool for studying aerosol‐cloud‐precipitation interactions.